2018
DOI: 10.1029/2018gl080264
|View full text |Cite
|
Sign up to set email alerts
|

Observational Relationship Between Entrainment Rate and Environmental Relative Humidity and Implications for Convection Parameterization

Abstract: Entrainment rate is a critical but highly uncertain quantity in convective parameterizations; especially, the effects of environmental relative humidity on entrainment rate are controversial, or even opposite, in different studies. Analysis of aircraft observations of cumuli from the Routine AAF (Atmospheric Radiation Measurement [ARM] Aerial Facility) Clouds with Low Optical Water Depths (CLOWD) Optical Radiative Observations (RACORO) and Rain in Cumulus over the Ocean (RICO) field campaigns shows that entrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 76 publications
(130 reference statements)
8
29
0
Order By: Relevance
“…Mean values (over the cloud depth) of ε , δ , and M are varied as a function of the environmental RH of different simulations and are presented in Figure . It is found that ε , δ , and M could be approximated linearly related to the RH where a positive correlation between ε and RH is observed, which was suggested in some previous studies (Lu et al, ; Stirling & Stratton, ). However, a negative correlation is seen between δ and RH as observed previously by Böing et al ().…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Mean values (over the cloud depth) of ε , δ , and M are varied as a function of the environmental RH of different simulations and are presented in Figure . It is found that ε , δ , and M could be approximated linearly related to the RH where a positive correlation between ε and RH is observed, which was suggested in some previous studies (Lu et al, ; Stirling & Stratton, ). However, a negative correlation is seen between δ and RH as observed previously by Böing et al ().…”
Section: Resultssupporting
confidence: 84%
“…Some LES studies have found that the entrainment rate becomes higher as the environmental RH is higher (Axelsen, ; Stirling & Stratton, ). Similarly, Lu et al () also found from the aircraft observations that the entrainment rate is positively correlated with the RH. However, Bechtold et al () and Zhao et al () using a climate model argued that the entrainment rate and RH are negatively correlated in deep convection.…”
Section: Introductionmentioning
confidence: 99%
“…4): in drier environments, a larger fraction of entrained air becomes negatively buoyant and detrains, leaving a smaller but less dilute cloud core. This trend is consistent with the observations of Lu et al (2018) and the simulations of Stirling and Stratton (2012) and Bera and Prabha (2019), but inconsistent with Derbyshire et al (2004) Moreover, cloud dilution was found to be strongly sensitive to continentality, with fractional dilution rates in maritime clouds about twice those in continental clouds. To explain this sensitivity, a similarity theory of shallow-cumulus transports based on the turbulent-kinetic-energy (TKE) budget was used (Grant and Brown, 1999;Grant and Lock, 2004;Kirshbaum and Grant, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…The buoyancy-sorting concept provides a useful physical explanation of the sensitivity of cloud dilution to cloud-layer RH found herein, as well as that in the numerical simulations of Stirling and Stratton (2012) and Bera and Prabha (2019) and the observations of Lu et al (2018). For a given amount of cloud-environmental mixing, a smaller fraction of entrained air becomes negatively buoyant and detrains in moister environments, resulting in more diluted cloud cores.…”
Section: Discussionsupporting
confidence: 60%
“…The above discussion indicates that, while the controls on shallow-cumulus entrainment and dilution are an active area of research, at least some of the environmental sensitivities and corresponding physical explanations of this process are either poorly understood or differ between different studies. Improving this understanding is essential given that the representation of cumulus convection, and particularly the entrainment process, is a major source of global climate sensitivity in those models (e.g., Murphy et al, 2004;Knight et al, 2007;Sanderson et al, 2008;Rougier et al, 2009;Klocke et al, 2011). In both global climate and many weather forecast models, shallow cumuli are parameterized due to insufficient grid resolution and will continue to be parameterized for some time.…”
Section: Introductionmentioning
confidence: 99%